"First Aid for Scalds" campaign: reaching Sydney's Chinese, Vietnamese, and Arabic speaking communities. Issue 2 (1st June 1999) - King, Lesley; Thomas, Margaret; Gatenby, Kristen; Georgiou, Angela; Hua, Myna
Abstract : Objectives —As a serious yet preventable problem, scald injuries in children have been a priority for prevention in Australia and other developed countries. Not only can the occurrence of scalds be prevented, but immediate first aid treatment offers an effective method for secondary prevention, reducing the severity of scalds. Despite the success of scald prevention initiatives, local evidence suggested that first aid knowledge was lacking in some minority ethnic groups. To redress this gap, the "First Aid for Scalds" campaign for those from a non-English speaking background was specifically targeted to three ethnic groups (Vietnamese, Chinese, and Arabic), with the aim of increasing the proportions of parents and caregivers who had correct knowledge of first aid treatment for scalds. The primary strategy was a media campaign, including advertisements on ethnic radio and in ethnic newspapers. Methods —The evaluation design included formative research and impact evaluation. The impact evaluation study involved random population based telephone surveys with each of the three language groups, before and after the campaign, to assess the reach and effectiveness of the campaign. Results —After the campaign, there were significant increases in the proportion of people who knew the correct first aid treatment for scalds. There were substantial variations in campaign recall and knowledge between each of the three language groups. The largest improvement was found in the Vietnamese group. Conclusion —The association between campaign recall and increase in correct knowledge, and the absence of any similar interventions during the campaign period, give credence to the conclusion that the changes observed were a result of the campaign. The results demonstrate the value of community based injury prevention campaigns specifically targeting linguistically diverse communities.